Hydrogen-Rich Water Ameliorates Autistic-Like Behavioral Abnormalities in Valproic Acid-Treated Adolescent Mice Offspring - Guo, Qingjun; Yin, Xi; Qiao, Meng; Jia, Yujiao; Chen, Dandan; Shao, Juan; Lebaron, Tyler W.; Gao, Yuan; Shi, Haishui; Jia, Bin (Frontiers in Behavioral Neuroscience, 2018)
Due to its anti-inflammatory and anti-oxidative effects, recent research has demonstrated that molecular hydrogen can serve as a new medical approach for depression, anxiety, and traumatic brain injury. However, its potential effects on neurodevelopmental diseases, such as autism are still elusive. The present study aims to investigate the potential effects of hydrogen-rich water (HRW) administration on valproic acid (VPA)-induced autistic-like behavioral deficits, and the associated underlying mechanism in adolescent mice offspring. Pregnant ICR mice were randomly divided into 5 groups (n=6). One group was injected with saline (NAV group) and provided hydrogen-free water. The other 4 groups were injected with VPA (600mg/kg, intraperitoneally, i.p.) on pregnant day (PND) 12.5. One group was provided with hydrogen-free water (VEH group) and the other three groups were provided HRW at different segments, PND 1 to PND 21 (PHV group), PND 13 to PND21 (PVS group) or from PND 13 to postnatal day 42 (PVL group). Behavioral tests, including open field, novelty suppressed feeding, hot plate, social interaction, and contextual fear memory tests were conducted between postnatal day 35-42. We found that HRW administration significantly reversed the autistic-like behaviors induced by maternal VPA exposure in the adolescent offspring of both male and female adolescent offspring. Furthermore, HRW administration significantly reversed the alternation of serum levels of IL-6 and TNF-α, but without any effects on the BDNF levels in maternal VPA-exposed mice offspring. These data suggest the need for additional research on HRW as a potential preventive strategy for autism and related disorders.